Ritual Word on Tradition of Lukah Gilo Society Bonai Regency Of Rokan Hulu: Antropolinguistik Study - Nofrita, Misra; Hermawan, Hermawan; Putri, Delia (Proceedings of the UR International Conference on Educational Sciences, 2018)
This article contains about the speech on the tradition of gilo, Rokan upstream regency studied in terms of anthropolinguistics. Anthropolinguistic studies here are more on texts in oral tradition by using the Van Dijk theory that classifies oral tradition texts into three structures, namely macro, superstructure and micro. There is also a method used is descriptive method. Descriptive method is a method used to examine an object, a thought or an event in the present. The result of the research shows that the speech in gilo tradition viewed by thematic or theme. The text spelled in the tradition of Lukah Gilo contains two themes namely the theme of divinity and the theme of the body. It is also reviewed the superstructure that can be viewed in order of spells read by Bomo. There are three stages of the mantra that Bomo reads: the first stage begins with a prayer (early stage), then the contents of the mantra and the cover of the mantra.